2015
DOI: 10.1155/2015/657570
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SNCA and FBN1 Methylation in the Stool as a Biomarker for Colorectal Cancer

Abstract: Aim. We examined the methylation status of SNCA and FBN1 genes in patients' paired tissue and stool samples for detection of colorectal cancer (CRC). Patients and Methods. 89 DNA tissue samples (normal/cancer) and corresponding stool samples were analyzed in our study. In addition, 30 stool samples were collected as healthy controls. Results. The methylation level of those samples was measured by methylation-specific polymerase chain reaction (MSP). The result shows that compared with the paired controls, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Previous studies have shown that expression of SNCA is regulated by hypermethylation of the CpG island in its promoter region in various human cancers . Demethylation drug treatment in MB cells showed reversed expression of this gene, suggesting that the silenced expression of SNCA might be due to epigenetic regulation, including DNA hypermethylation (Figure A).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have shown that expression of SNCA is regulated by hypermethylation of the CpG island in its promoter region in various human cancers . Demethylation drug treatment in MB cells showed reversed expression of this gene, suggesting that the silenced expression of SNCA might be due to epigenetic regulation, including DNA hypermethylation (Figure A).…”
Section: Resultsmentioning
confidence: 83%
“…It has been reported that SNCA expression is regulated by epigenetic mechanisms in a series of human cancers, including cholangiocarcinoma, colorectal cancer, and non‐Hodgkin's lymphoma . Bethge et al reported that SNCA methylation might be suitable for early detection and monitoring of non‐Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the efficiency of cell wall lysis of gram-positive bacteria in the feces, the samples were incubated at 95°C for 5 minutes. The extracted DNA was stored at -20°C until processed (24).…”
Section: Dna Extraction 16s Rrna Gene Amplification and Sequencingmentioning
confidence: 99%
“…The discovery of the presence of DNA in fecal and urine samples [46] and circulating nucleosomes in serum [47,48] has led to the foundation of identifying epigenetic markers such as DNA methylation and histone posttranslational modification for cancer diagnosis. Ahlquist et al [49] demonstrated the recovery of DNA from frozen fecal samples of colorectal cancer patients which was followed by other investigators showing matching DNA methylation patterns between DNA from tissue and fecal samples of gastric and colorectal cancer patients [50][51][52] . Methylation pattern of DNA isolated from urine samples was also used to diagnose bladder and prostate cancer [53][54][55][56][57] .…”
Section: Histone Ptms In Cancermentioning
confidence: 88%